Research Trends and Prospects of Green Economy in Economic Literature: A Bibliometric Analysis - Nur Rizky Putri Mahadi; Mega Ilhamiwati; Eko Sudarmanto (West Science Social and Humanities Studies, 2024)
Over the past few decades, the global discourse on environmental sustainability and climate change has catalyzed a profound transformation in economic paradigms, giving rise to the concept of the green economy. This paradigm emphasizes the integration of economic activities with environmental preservation and social equity to achieve sustainable development goals. As scholarly interest and research output in the green economy burgeon, navigating through the vast body of literature becomes increasingly challenging. In response, this study conducts a bibliometric analysis of economic literature related to the green economy, aiming to map out research trends, identify influential authors, seminal works, and thematic clusters. Employing bibliometric techniques such as co-citation analysis, keyword analysis, and citation mapping, this research provides insights into the intellectual landscape of the green economy field. The analysis reveals key research gaps, such as uneven geographical distribution and the need for interdisciplinary studies, while also highlighting emerging areas of inquiry. By delineating future research trajectories, this study aims to inform policymakers, stakeholders, and researchers striving towards sustainable economic development goals.